Effect of Calcium and Vitamin D Supplements as an Adjuvant Therapy to Metformin on Menstrual Cycle Abnormalities, Hormonal Profile, and IGF-1 System in Polycystic Ovary Syndrome Patients: A Randomized, Placebo-Controlled Clinical Trial - Sally Kadoura; Marwan Alhalabi; Abdul Hakim Nattouf (Hindawi Limited, 2019)
Objective. This study aims to investigate the effect of combining calcium and vitamin D supplements with metformin on menstrual cycle abnormalities, gonadotropins, and IGF-1 system in vitamin D-deficient/insufficient PCOS women. Study Design. This is a randomized, placebo-controlled clinical trial. Setting. This study was performed in Damascus University of Obstetrics and Gynecology Hospital and Orient Hospital, in Damascus, Syria. Materials and Methods. Forty PCOS women with 25-OH-vitamin D < 30 ng/ml were randomly assigned to take either metformin (1500 mg/daily) plus placebo or metformin (1500 mg/daily) plus calcium (1000 mg/daily) and vitamin D3 (6000 IU/daily) orally for 8 weeks. Serum levels of gonadotropins (luteinizing hormone (LH) and follicle-stimulating hormone (FSH)), insulin-like growth factor-1 (IGF-1), and insulin-like growth factor binding protein-1 (IGFBP-1) were detected at the baseline during the early follicular phase of a spontaneous or induced menstrual cycle and after 8 weeks of intervention (except for the final gonadotropins levels which were assayed from samples obtained during the early follicular phase of a spontaneous menstrual cycle). Results. Thirty-four patients (85%) completed the study. After 8 weeks of intervention, calcium and vitamin D co-supplementation led to a significant increase in 25-OH-vitamin D levels and calcium levels in the supplementation group compared to the other group (change in 25-OH-vitamin D levels: +19.38 ± 7.78 vs +0.11 ± 4.79 ng/ml, respectively; p value=0.0001) (change in calcium levels: +0.83 ± 0.82 vs +0.01 ± 0.86 mg/dl, respectively; p value=0.014). An improvement in menstrual cycle irregularity was detected in 38.5% and 58.8% of patients in metformin-placebo group and metformin-calcium-vitamin D group, respectively; but the change was statistically significant only in the supplementation group (p value=0.002). Nevertheless, the means of changes from baseline in gonadotropins levels (serum levels of LH, FSH, and LH to FSH ratio) and the studied parameters of IGF-1 system (serum levels of IGF-1, IGFBP-1, and IGF-1 to IGFBP-I ratio) did not differ significantly between the two groups. Conclusions. Calcium and vitamin D supplements can support metformin effect on regulation of menstrual cycle irregularity in vitamin D-deficient/insufficient PCOS patients, but this effect is not associated with any significant changes in gonadotropins or IGF-1 system. These results suggest a possible role of calcium and vitamin D supplements in managing PCOS. However, further studies are needed to identify the underlying mechanisms. The Clinical Trial Registration Number is NCT03792984.